Influência de parâmetros de recozimento contínuo sobre a evolução microestrutural de um aço bifásico - Fernando de Souza Costa (2012)
The microstructural changes during the intercritical annealing cycle of a dual phase C-Mn steel was studied, with emphasis on the ferrite recrystallization, the austenite formation, during the stages of heating and soaking, and new ferrite formation, which occurs during cooling. Through the use of the thermo-mechanical simulator Gleeble 3500 model and as well as the dilatometer Bähr Dil 805 several simulations were performed the steps of heating, soaking and cooling of an intercritical annealing cycle. The influence of the overaging step, however, was not studied. The manganese partitioning was also investigated through the resources of SEM/EDS and WDS. From isothermal tests performed at temperatures of 600, 650, 680 and 710°C the value of activation energy associated with the ferrite recrystallization was estimated in 310 ± 22 kJ/mol. The recrystallization kinetics was mathematically adjusted to the JAMK model. The use of different heating rates, of 3.8°C/s, 10°C/s and 100°C/s, did not significantly affect temperatures Ac1and Ac. Ac3, on the other hand, systematically increased with the heating rate. The increase in heating rate also increased the microstructural banding due to the predominance of growth mechanisms of the austenite over the nucleation. The influence of the soaking temperature over the distribution of the 2nd phase constituent particles along the microstructure was observed. On 740°C soaking temperature, the distribution occurred along the ferrite grain boundaries. Increasing temperature, however, there was a progressive increase from this distribution also in the interior of ferrite grains. There was also a decrease in the ferrite grain size when the soaking temperature was held at 800°C and 820°C, temperatures which are near the austenitic field. These two effects have been explained in the light of the significant amount of new ferrite formed during cooling, over 50% for these two temperatures soaking. Moreover, the results obtained in this study gave the basis of the assumption that, besides epitaxial formation by moving the interfaces / , which is currently the most accepted mechanism for new ferrite formation, has also occurred nucleation and growth of new ferritic grains at these two temperatures, this being the mechanism responsible for the reduction of the ferrite grain size.